GE_GERICHTE P/19851/2021 vom 27. Juni 2023 - GE Cour de justice (2023)
FIXATION DE LA PEINE;VOL(DROIT PÉNAL);INFRACTION PAR MÉTIER;CONCOURS D'INFRACTIONS | CP.139.ch1 et 2; CP.144.al1; CP.186; CP.291.al1; CP.47